From the Vineyard of Attainment - MacCallum, F. Lyman (The Muslim world, 1930)
[Yakup Kadri Bey, author of the following elegy, is one of the leading modem Turkish authors. Early in life he is believed to have had close relations with the Bektashi order of Dervishes in the vicinity of his home near Smyrna About eight years ago he published a book, “Nur Baba” in which he claims to revcal the darker side of life in the Bektashi monasteries. “Sodom and Gomorrah”, his most recent book, performs the same grimy service for the Allied A m y of Occupation, which spent an uneasy four years in Constantinople. His little book, “From the Vineyard of Attainment”, consists of a dozen such entreaties as the foIIowing, in all of which the disillusion and pessimism of the Bektashi finds beautiful and poignant expression. Those who have attained to a true knowledge of, or come into union with God, have reached the Vineyard of Attainment.—Translator.]